Preservando e educando: o tratamento dado ao lixo na comunidade ribeirinha do rio Quianduba - RODRIGUES, Marenilda Oliveira (2024)
This work seeks to analyze and discuss the issues related to environmental and social impacts generated by the irregular deposit waste on the islands of Abaetetuba, particularly in Rio Quianduba. Because there is no transportation waterway for selective waste collection in the islands of the municipality, the waste is dumped directly into rivers, contaminating the water and kills around the islands. For the preparation of this work were performed bibliographic, field research, through interviews with community residents and with the coordination of the Environment for the City of Abaetetuba and analysis of an environmental project, prepared by teachers from Our Lady of Perpetual Help (Rio Quianduba) and applied to students and residents of the island, to obtain information from the research area. After research, we found that the families began to get other habits customs concerning litter. This work was rewarding because sensitized the families of Rio Quianduba to have knowledge of how important solid waste management, where the children have already tried to explain to their parents the danger that they bring to the environment and human health.